2020
DOI: 10.5187/jast.2020.62.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine and valine differentially stimulate milk protein synthetic and energy-mediated pathway in immortalized bovine mammary epithelial cells

Abstract: Studies on promoting milk protein yield by supplementation of amino acids have been globally conducted. Nevertheless, there is a lack of knowledge of what pathways affected by individual amino acid in mammary epithelial cells that produce milk in practice. Phenylalanine (PHE) and valine (VAL) are essential amino acids for dairy cows, however, researches on mammary cell levels are still lacking. Thus, the aim of this study was conducted to evaluate the effects of PHE and VAL on milk protein synthesis-related an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Phenylalanine (Phe) was confirmed as a potentially limiting amino acid for milk protein synthesis in BMECs [ 40 ]. The extraction of Phe by the mammary gland was shown to be equal to its amount secreted in milk [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine (Phe) was confirmed as a potentially limiting amino acid for milk protein synthesis in BMECs [ 40 ]. The extraction of Phe by the mammary gland was shown to be equal to its amount secreted in milk [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of HMBi upregulated the elongation protein eukaryotic translation initiation factor 3 subunit (EIF3A) but downregulated the ribosomal proteins RPS12 and RPS21. Supplementation with D-Met stimulated phosphoinositide 3 (PI3) kinase, an upstream mTOR activator [ 19 , 28 , 33 , 34 ]. The list of all upregulated and downregulated proteins are listed in Tables 8 and 9 .…”
Section: Resultsmentioning
confidence: 99%
“…We found Val acutely stimulated β-casein synthesis in the BMECs in a dose-dependent manner, especially at concentrations of 1.2 and 0.8 mM, while Val absence inhibited β-casein synthesis. However, Kim et al found that β-casein expression increased only at Val concentrations of 0.3 and 1.5 mM. Further studies are needed to investigate the underlying mechanisms by which Val affects β-casein synthesis.…”
Section: Discussionmentioning
confidence: 98%